Set-theoretic model of the telemedicine with patient state consideration - Strykhaliuk, Bohdan; Kolodij, Roman; Olexin, Mykhailo (Видавництво Львівської політехніки, 2012)
it is developed set-theoretic model for the system of telemedicine services.
Keywords: telemedicine; set-theoretic model; emergent telemedicine services